Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.jafc.6b02891
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Soluble Grape-Derived Proteins to Condensed Tannin Extractability during Red Wine Fermentation

Abstract: In red winemaking, the extractability of condensed tannins (CT) can vary considerably even under identical fermentation conditions, and several explanations for this phenomenon have been proposed. Recent work has demonstrated that grape pathogenesis-related proteins (PRPs) may limit retention of CT added to finished wines, but their relevance to CT extractability has not been evaluated. In this work, Vitis vinifera and interspecific hybrids (Vitis ssp.) from both hot and cool climates were vinified under small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 51 publications
(104 reference statements)
1
36
0
Order By: Relevance
“…In comparison with the H‐3 Control, the tannin concentration in the H‐1 and H‐2 wines was 59 and 52% lower at pressing, respectively, and these differences were retained at the end of MLF. A slight loss in tannin concentration occurred over time, however, likely due to precipitation and/or adsorption via interactions with yeast cells, protein or cell wall material (Pérez‐Serradilla and Luque de Castro , Springer et al , Bindon et al ) (Table , Figure b). Analysis of tannin composition revealed that wine tannin from H‐1 and H‐2 had a significantly lower molecular mass (and corresponding mDP) than that observed for wine tannin from the H‐3 treatment, which was confirmed using both the phloroglucinolysis (subunit composition) and GPC (size distribution) techniques (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with the H‐3 Control, the tannin concentration in the H‐1 and H‐2 wines was 59 and 52% lower at pressing, respectively, and these differences were retained at the end of MLF. A slight loss in tannin concentration occurred over time, however, likely due to precipitation and/or adsorption via interactions with yeast cells, protein or cell wall material (Pérez‐Serradilla and Luque de Castro , Springer et al , Bindon et al ) (Table , Figure b). Analysis of tannin composition revealed that wine tannin from H‐1 and H‐2 had a significantly lower molecular mass (and corresponding mDP) than that observed for wine tannin from the H‐3 treatment, which was confirmed using both the phloroglucinolysis (subunit composition) and GPC (size distribution) techniques (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Further to the hypothesis that the proportion of mesocarp material may have changed within diluted ferments, other significant must components which may have been affected by water addition were potentially proteins and polysaccharides, given that the acidity and nutrient status of the musts were maintained. In V. vinifera grapes and more importantly in certain US hybrid grape cultivars the presence of a significant quantity of grape protein has been found to limit both the extraction and the retention of tannin in red wine (Springer et al 2016). The role of grape protein in limiting tannin retention during fermentation is a relatively new research area; therefore, the potential effect of adding water to must on the phenomenon of protein-tannin precipitation would be speculative at best, but should nonetheless be considered as a possible factor within the solvent matrix which might be affected by water addition.…”
Section: Implications Of Water Addition To Must On the Concentration mentioning
confidence: 99%
“…We already knew that the transfer rate of phenolic compounds from grape to must is limited due to, among other reasons, the interactions that occur between phenolic compounds and the skin and pulp cell walls present in the must in large concentrations, interactions that prevent these pigments from contributing to the final wine phenolic content [2,3]. Another potential mechanism has been identified in which extracted grape tannins may be lost from must/wine during vinification, and this is as a precipitate with solubilized grape proteins [51,52]. These authors stated that although protein is, in general, a minor component in terms of total concentration, losses of tannins via precipitation with proteins could be in the order of 50% of available tannins.…”
Section: The Role Of Soluble Polysaccharides In the Chromatic And Senmentioning
confidence: 99%
“…The addition of oenological tannins or the use of oak chips has been described by many authors as a positive attribute in wine production (Olga Pascual et al, 2016;Springer et al, 2016;Bilko et al, 2019). Related to this fact the subject of this study is to evaluate these components using stems and oak chips instead of oenological products with the purpose to increase the content of tannins in the wine, in order to achieve stabilization of the wine color during the fermentation steps and their effect on Received: January 10, 2020; accepted: March 5, 2020…”
Section: Introductionmentioning
confidence: 99%